TAFSIR AL-QUR'AN DAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Ulil Albab (AL-BAYAN INSTITUTE, 2022)
This article explores the role of Qur'anic teachings in supporting the achievement of the Sustainable Development Goals (SDGs) in Muslim-majority countries. Focusing on Qur'anic verses relevant to contemporary social issues, the article analyzes how Islamic values on social justice, poverty alleviation, education and gender equality can provide an ethical foundation for sustainable development policies. The study uses a qualitative-descriptive approach, integrating classical and contemporary commentaries with UN reports on the implementation of the SDGs in Muslim countries. One important finding is how the concepts of zakat and waqf, as forms of Islamic social finance, can support the achievement of SDG 1 (No Poverty) and SDG 4 (Quality Education), especially through effective zakat management in Indonesia and Malaysia. In addition, the article also highlights the Green Hajj initiative in Saudi Arabia that supports SDG 13 (Climate Action) by reducing the carbon footprint during the pilgrimage. However, major challenges remain, including inequality in wealth distribution, patriarchal culture, and political instability. Therefore, synergy between religious teachings, government policies, and international cooperation is needed to overcome these barriers. As such, this article contributes to the understanding of how Islamic values can be implemented in support of sustainable global development.